2021
DOI: 10.3332/ecancer.2021.1169
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy screening practices and treatment of pregnant patients among radiation oncologists: results of an international survey

Abstract: Background:The human embryo or foetus is susceptible to harmful effects of radiation, which include growth delay, malformations, impaired cognitive function, cancer and foetal demise. The purpose of this study is to describe pregnancy screening practices in radiation oncology, so that potential health effects may be avoided and areas of prevention may be identified.Methods: An electronic survey was delivered to 6,304 members of the American Society for Radiation Oncology. The survey subjects were radiation onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…Demographic data, including education level and language barriers, were not readily ascertainable from patient records, which limited the generalisability of our findings. However, our population size and results support the existing published experience that pregnancy screening is performed rarely prior to treatment 6,12–14,24 …”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Demographic data, including education level and language barriers, were not readily ascertainable from patient records, which limited the generalisability of our findings. However, our population size and results support the existing published experience that pregnancy screening is performed rarely prior to treatment 6,12–14,24 …”
Section: Discussionsupporting
confidence: 86%
“…However, our population size and results support the existing published experience that pregnancy screening is performed rarely prior to treatment. 6,[12][13][14]24…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2021 study noted that ASTRO radiation oncologists responding to an electronic survey indicated that they would “strongly agree” or “agree” that screening for pregnancy should be done prior to delivery of radiation therapy (84.8% of respondents), but 29.7% of respondents noted that their department did not have such a screening policy in place, and 7.1% of respondents indicated that their department did not screen for pregnancy. 4 The same survey indicated that having a departmental policy in place for screening for pregnancy was strongly correlated with respondents screening for pregnancy ( p = 0.0005). These results echo those of a 2016 survey of National Comprehensive Cancer Network member institutions, which found that 30% of respondents did not have a guideline or policy in place on screening patients for pregnancy prior to treatment via radiation therapy, surgery, or chemotherapy.…”
Section: Introductionmentioning
confidence: 94%
“…However, many radiation oncology departments do not systematically or routinely verify patient pregnancy status. A 2021 study noted that ASTRO radiation oncologists responding to an electronic survey indicated that they would “strongly agree” or “agree” that screening for pregnancy should be done prior to delivery of radiation therapy (84.8% of respondents), but 29.7% of respondents noted that their department did not have such a screening policy in place, and 7.1% of respondents indicated that their department did not screen for pregnancy 4 . The same survey indicated that having a departmental policy in place for screening for pregnancy was strongly correlated with respondents screening for pregnancy ( p = 0.0005).…”
Section: Introductionmentioning
confidence: 99%